Pirates - Clarke, Catriona; McKenna, Terry (London : Usborne ; [Tulsa, Okla. : EDC], 2006)
Illustrations and simple text describe pirates, their way of life, and the ships they sailed.
"Level 2"--Cover.
Includes index.
006-008.
Keywords: Pirates -- Juvenile literature